Hate, Oppression, Repression, and the Apocalyptic Style: Facing Complex Questions and Challenges - Chip Berlet (Journal of Hate Studies, 2004)
As we build the field of Hate Studies we need to scrupulously inspect our own work. Blee and Ferber have already suggested a number of complex questions for scholars to answer. This paper argues that understanding the interrelated dynamics of hate, apocalyptic dualism, institutionalized oppression, and political repression is crucial to increasing the accuracy and effectiveness of our research and answering these questions.